Cirip.Eu - An educational microblogging platform around objects 2.0 - Carmen Holotescu; Gabriela Grosseck (Firenze University Press, 2013)
In recent years, the most daring player in the social media arena proved to be the microblogging technology, the most energetic in this field being Twitter, raising the interest of the educational actors. A number of microblogging platforms dedicated to education were implemented, such as Edmodo, Plurk, Cirip.eu or Twiducate. In this context, the paper aims to provide an overall analysis of the microblogging platform Cirip.eu for educational directions such as: information and knowledge management, courses enhancement, delivering online courses, collaborative projects, communities of practice, hosting different workshops, conferences or scientific events, building e- portfolios, etc. Thus, the main aspects of the paper will regard the following: 1. The facilities offered by Cirip.eu recommend it as a modern and flexible mobile Social Learning Management System (mSLMS), integrating users' Personal Learning Environments; 2. How microblogging can be integrated with other Web2.0 technologies, and into the Open Educational Resources movement; 3. How the experience and the new pedagogical approach in using microblogging can be captured and formally represented as learning design objects; 4. How learning design objects can be shared, discussed, improved, reused on the microblogging platform.